Islamic Education in Pesantren: Between Quality, Idealism, or Capitalization - Siti Maryam Munjiat (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
This article aims to describe and analyze Islamic education in pesantren between the quality, idealism and capitalization of education. The method used in this article is a literature review by analyzing the books and journals relevant to the theme. The results of this study are: 1) the ideal Islamic boarding school is capable of forming santri morals, social competence and social skill. 2) Educational capitalization in pesantren should be avoided by applying Gardner's theory of intelligence. 3) The quality of the pesantren depends on the components of each other supporting each other, especially the learning process and curriculum integration that is carried out. 4) The quality of the pesantren does not always depend on the charismatic kiai.